Properties of Cobalt- and Nickel-Doped Zif-8 Framework Materials and Their Application in Heavy-Metal Removal from Wastewater - Shen, Bowen; Wang, Bixuan; Zhu, Liying; Jiang, Ling (Nanomaterials (Basel, Switzerland), 2020)
Heterometallic zeolite imidazole framework materials (ZIF) exhibit highly attractive properties and have drawn increased attention. In this study, a petal-like zinc based ZIF-8 crystal and materials doped with cobalt and nickel ions were efficiently prepared in an aqueous solution at room temperature. It was observed that doped cobalt and nickel had obviously different effects on the morphology of ZIF-8. Cobalt ions were beneficial for the formation of ZIF-8, while addition of nickel ions tended to destroy the original configuration. Then we compared the absorption ability for metal ions between petal-like ZIF-8 and its doped derivatives with anion dichromate ions (Cr2O72−) and cation copper ions (Cu2+) as the absorbates. Results indicated that saturated adsorption capacities of Co@ZIF-8 and Ni@ZIF-8 for Cr2O72− reach 43.00 and 51.60 mg/g, while they are 1191.67 and 1066.67 mg/g for Cu2+, respectively, which are much higher than the original ZIF-8 materials. Furthermore, both the heterometallic ZIF-8 materials show fast adsorption kinetics to reach adsorption equilibrium. Therefore, petal-like ZIF-8 with doped ions can be produced through a facile method and can be an excellent candidate for further applications in heavy-metal treatment.